Health education for preventing flour albus with personal hygiene practices of reproductive organs of female students in MAN Palangka Raya - WIDIARTI, ASTRI; Arifin, Syamsul; Lestarisa, Trilianty; Putra S, Ravenalla Abdurrahman Al Hakim Sampurna; Mutiasari, Dian; Widodo, Tri; Veronica, Anna Marthea; Toemon, Angeline Novia; Inarae, Gabriella (LPPM Universitas Palangka Raya, 2023)
Flour albus is a lot happening to female teenagers, which caused by lack of knowledge about the behavior of personal hygiene reproductive organs that are very influential in the occurrence of flour albus. Women who have less knowledge about the hygiene of reproductive organs will have an impact on the health of their reproductive organs because knowledge is a determining factor in maintaining the hygiene of reproductive organs, especially in the genitals. Health promotion with topics regarding personal hygiene reproductives organs and flour albus in MAN Palangka Raya city has long not have been done, therefore, health education on flour albus prevention needs to be given. The goal of giving students a health education is to improve knowledge and information related to the prevention of flour albus with the application of personal hygiene organs in the school students of MAN Palangka Raya City. A health education activity carried out in the high school of man city roadblocks.The activities carried out are the educational delivery of flour albus as well as the prevention of personal hygiene.After that, a Q&A session performed between the students and the activity team and followed by a Q&A session as well as a quiz gift. Students who participate in this activity experience improved knowledge of flour albus prevention with the application of personal hygiene practices of reproductive organs, as shown by an average increase in post test results, this is from the pre-test with an average of 5.92 to 7.12 when the post-test performed. Similar activities need to be carried out regularly to students of the MAN Palangka Raya City, that they can apply proper personal hygiene of reproductive organs in preventing flour albus.